Welding Competence Training at Dropout Youth - Refdinal, Refdinal; Ardi, Junil; Purwantono, Purwantono (Teknomekanik, 2019)
The problem with partners is drop out youth who do not have competence. The condition of the community dropping out of school and working as unskilled labourers has an impact on the low level of public welfare. The distance between the Dharmasraya district and the provincial capital has an impact on the contrast of the quality of education carried out which causes the community to not understand the importance of education. So that some of the human resources in Dharmasraya have become manual labourers in plantations and factories. The purpose of implementing this service activity is to provide a solution to the problems faced by the community, especially for school dropouts. Most of the dropout youths who are junior high school (SMP) level do not have special competencies that make them have added value. The work carried out by this young man is only limited to gardening and does not guarantee economic prosperity. Through this service activity, TIM strives to provide competency in the welding field that can be used to open a business that is much needed by the community. The training activities were designed for 3 days which will be held from October 12 to October 14 2018. The speakers in this activity were Drs. Purwantono, M.Pd, who has a BNSP level I welding certificate and the second speaker is Junil Adri, M.Pd.T who has a BNSP level III welding certificate. On the first day, the speaker will convey the basic concepts in the welding process and demonstrate how to make weld grooves and connect the plate in the welding process. On the second day, the speakers began to invite participants to design products that could be made through welding activities in accordance with the needs of the community. In this activity, TIM directed to make a trellis fence. TEAM began to guide participants in the process of making a trellis. On the third day, the TEAM provided direction on how to weld entrepreneurial opportunities in the field. The chairperson of the service with TIM asked the kenagarian to be able to accommodate the birth of new entrepreneurs for youth who could make independent and productive people.